Analisis Transformasi AI Customer Service (Chatbot) di Travel Agent X Pakuwon Mall - Dian Febrina Anggraeni; Rizki Adityaji (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implementation of Artificial Intelligence (AI)-based chatbots in customer service at a travel agency and its implications for operational efficiency, human-AI work patterns, and organizational adaptability. The study employed a qualitative approach with a single-case study design, collecting data through in-depth interviews with relevant staff, observing customer service processes, and analyzing thematically obtained data. The results indicate that the use of chatbots improves operational efficiency by automating routine tasks and reducing staff workload. Another key finding is the development of a hybrid service model, where chatbots handle basic questions while human staff focus on complex services that require judgment and empathy. However, the chatbot's limitations in understanding conversational context and emotional aspects remain a challenge. The implications of this study emphasize that the success of implementing AI in customer service is determined not only by technology but also by the organization's readiness to develop digital competencies and continuously update systems, so that human and AI collaboration can run optimally.